Membentuk Profil Siswa Pancasila Melaui Pengajaran Bahasa Indonesia di SMA Budisatrya Medan - Nur Hidayah Hasibuan; Muhammad Iraqi Fauzi; Tri Bayu Armanda; Dyna MT Pasaribu; Hendra Kurniawan Pulungan (Universitas Palan, 2024)
This research aims to determine the role of teachers in shaping the role of Pancasila through Indonesian language learning for students at SMA Budistrya Medan. This research is research that uses a qualitative approach. The data collection technique uses a questionnaire which contains the types of questions that will be distributed. The research subjects or informants involved in this research were teachers and students of Medan Budisatrya High School. The data analysis techniques used are data collection, data reduction, data display, and drawing conclusions. The results of this research show that the role of teachers is in shaping the role of Pancasila through learning Indonesian at SMA Budistrya Medan. among other things, providing meaning to the values of the Pancasila principles which can be implemented in everyday life.